Immunomodulatory Properties of Pomegranate Peel Extract in a Model of Human Peripheral Blood Mononuclear Cell Culture - Miodrag Čolić; Marina Bekić; Sergej Tomić; Jelena Đokić; Dušan Radojević; Katarina Šavikin; Nataša Miljuš; Milan Marković; Ranko Škrbić (MDPI AG, 2022)
Pomegranate peel extract (PoPEx) has been shown to have antioxidant and anti-inflammatory properties, but its effect on the adaptive immune system has not been sufficiently investigated. In this study, the treatment of human peripheral blood mononuclear cells (PBMC) with PoPEx (range 6.25-400 µg/mL) resulted in cytotoxicity at concentrations of 100 µg/mL and higher, due to the induction of apoptosis and oxidative stress, whereas autophagy was reduced. At non-cytotoxic concentrations, the opposite effect on these processes was observed simultaneously with the inhibition of PHA-induced PBMC proliferation and a significant decrease in the expression of CD4. PoPEx differently modulated the expression of activation markers (CD69, CD25, ICOS) and PD1 (inhibitory marker), depending on the dose and T-cell subsets. PoPEx (starting from 12.5 µg/mL) suppressed the production of Th1 (IFN-γ), Th17 (IL-17A, IL-17F, and IL-22), Th9 (IL-9), and proinflammatory cytokines (TNF-α and IL-6) in culture supernatants. Lower concentrations upregulated Th2 (IL-5 and IL-13) and Treg (IL-10) responses as well as CD4+CD25hiFoxp3+ cell frequency. Higher concentrations of PoPEx increased the frequency of IL-10- and TGF-β-producing T-cells (much higher in the CD4+ subset). In conclusion, our study suggested for the first time complex immunoregulatory effects of PoPEx on T cells, which could assist in the suppression of chronic inflammatory and autoimmune diseases.